Effects of pH, dosage and contact time on boron removal from synthetic saline water using Moringa oleifera seeds - Jami, Mohammed Saedi; Zakaria, Nur Syahirah; Ahmed, Moussa Mohamed; Nik Abdul Ghani, Nik Rashida; Ngabura, Mohammed; Ahmad, Mani Malam (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Boron is one of the key elements required in flora, fauna, as well as human beings. However, human life and eco-systems could be seriously affected when exposed to excessive levels of boron, especially in seawater and groundwater. In this work Moringa oleifera was selected as a precursor adsorbent owing to its eco-friendliness characteristics and favourable removal efficiency of adsorbates. Besides, M. oleifera does not significantly affect the conductivity of water and pH value after the treatment. The main aim of this work was to investigate the potentiality of M. oleifera in the treatment of boron from contaminated saline water. The effect of adsorption parameters such as pH (7 - 9), adsorbent dose of 4000 – 8000 mg/L of solution and contact time of 60 – 180 min was thoroughly investigated. Face-centred Central Composite Design (FCCCD) was applied to optimize these parameters. Consequently, the highest percentage of removal (65%) was achieved at the pH of 8, 120 min of contact time and 6000 mg/L of adsorbent dosage. The adsorption studies stated that the adsorption fitted well with the Freundlich isotherm. Therefore, the outcome of this work revealed that boron could be significantly treated using a prepared adsorbent from M. oleifera. ******************************************************************************** Boron merupakan salah satu elemen yang diperlukan oleh flora, fauna, juga manusia. Walau bagaimanapun, hidup manusia dan ekosistem pasti terkesan apabila di dedahkan secara berlebihan, terutama pada air di lautan dan daratan. Kajian ini menggunakan Moringa oleifera sebagai penjerap kerana ia mempunyai ciri-ciri mesra dan berkesan membuang bahan terjerap dengan berkesan. Selain itu, M. oleifera tidak langsung memberi kesan kepada konduktiviti air dan nilai pH selepas perawatan. Tujuan utama kajian ini adalah mengkaji potensi M. oleifera dalam larutan rawatan air garam boron yang tercemar. Kesan parameter penjerapan seperti pH (7-9), dos penjerapan 4000 – 8000 mg/L larutan dan masa interaksi 60 – 180 minit di kaji dengan teliti. KaedahKomposisi Tumpuan Tengah Muka (FCCCD) digunakan bagi mengoptimumkanparameter-parameter ini. Hasilnya, peratus tertinggi penyingkiran adalah sebanyak (65%)pada pH 8, 120 min masa interaksi dan 6000 mg/L dos penjerapan. Kesimpulannya, kajianpenjerapan ini menyokong kuat teori isoterma Freundlich. Oleh itu, hasil kajian inimenunjukkan boron dapat dirawat dengan menggunakan larutan penjerapan daripada M.oleifera.12